SOCCER SEASONAL VARIATIONS IN SPRINT MECHANICAL PROPERTIES AND VERTICAL JUMP PERFORMANCE (Kinesiology, 2018)
The aim of this study was to quantify possible differences in countermovement jump (CMJ) height, sprint performance and underlying mechanical properties as a function of time during a soccer season. Fortyfour male professional soccer players were identified in the Norwegian Olympic Federation’s test database. Each of these players had performed 40-m sprint and CMJ tests at least once within pre-season, in-season and off-season over the course of one year. The players sprinted, possibly to most likely, faster over 40 m during off-season compared to in-season (mean difference, ±90%CL: 0.04, ±0.03 s; small) and pre-season (0.08, ±0.02 s; small). Maximal horizontal power production was likely to most likely greater off-season compared to in-season (mean difference, ±90%CL: 0.5, ±0.4 W∙kg-1; small) and pre-season (0.8, ±0.4 W∙kg-1; small). Maximal horizontal force production was likely greater off-season compared to in-season (0.2, ±0.2 N∙kg-1; small). Theoretical maximal velocity obtained during pre-season was, possibly to very likely, lower compared to in-season (0.09, ±0.12 m∙s-1; small) and off-season (0.14, ±0.09 m∙s-1; small). The force-velocity slope values relative to body mass were, possibly to likely, higher off-season compared to in-season (0.02, ±0.03; small) and pre-season (0.01, ±0.02; small). CMJ results obtained off-season were, likely better, than those for pre-season (1.2, ±0.6 cm; small). The present study shows that anaerobic fitness variables, believed to be relevant for the on-field soccer performance, are sensitive to the varying season times. Key words: accelerated sprinting, maximal velocity sprinting, horizontal power production, force-velocity profile